Making It in a Cover Music Scene: Negotiating Artistic Identities in a "Kmart‐Level Market". Issue 1 (5th December 2016) - Scarborough, Roscoe C.
Abstract : This research examines how musicians understand art and commerce in a music scene dominated by cover bands. Drawing on thirty semi‐structured interviews and one hundred hours of ethnographic observation, I find that most musicians self‐identify as artists yet perceive social status to be rooted in commercial success. This research details what it means to "make it" in an art world that offers little institutional support or remunerative reward for artistry. Musicians employ three approaches to negotiate the disconnect between artistic identities and commercially defined status: segregating their artistic and commercial pursuits, locating artistry in their commercial work, and justifying their commercially viable activities as a means to attaining a comfortable lifestyle. This on‐the‐ground account of commercial influences' effects on musicians informs post‐Bourdieusian research on fields of cultural production. I suggest that future research on culture producers must distinguish between social status—a position in a social hierarchy—and interpersonal respect. When esthetics are marginalized as a basis for status, musicians' status becomes bound to employment opportunities and expansible relative to the extent of the scene.